# If f(x) = 3x + 2 and g(x) = 2x - 2, what is (f - g)(x)?

**Solution:**

Given functions:

f(x) = 3x + 2

g(x) = 2x - 2

We have to find (f - g)(x)

We know that

(f - g)(x) = f(x) - g(x)

Substituting the values

= (3x + 2) - (2x - 2)

By further simplification

= 3x + 2 - 2x + 2

= x + 4

Therefore, the value of (f - g)(x) = x + 4.

## If f(x) = 3x + 2 and g(x) = 2x - 2, what is (f - g)(x)?

**Summary:**

If f(x) = 3x + 2 and g(x) = 2x - 2, the value of (f - g)(x) is x + 4.

Math worksheets and

visual curriculum

visual curriculum